2004
DOI: 10.1007/s10433-004-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Disability-free life expectancy: a cross-national comparison of six longitudinal studies on aging. The CLESA project

Abstract: Disability-free life expectancy (DFLE) was compared in six countries taking part in the Crossnational Determinants of Quality of Life and Health Services for the Elderly (CLESA) project. Data from six existing longitudinal studies were used: TamELSA (Tampere, Finland), CALAS (Israel), ILSA (Italy), LASA (The Netherlands), Aging in Legane´s (Legane´s, Spain) and SATSA (Sweden). A harmonised four-item disability measure (bathing, dressing, transferring, toileting) was used to calculate DFLE; the harmonised measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
3
30
0
1
Order By: Relevance
“…No significant changes in disability in Finland and declining disability prevalence have been reported in Spain (7). The CLESA collaborative study reports longer life expectancies and lower disability-free life expectancy in the older populations of Southern Europe than those in Northern Europe (8). To our knowledge, there is no report using longitudinal data on functional trends of the older population in Southern Europe.…”
Section: Introductionmentioning
confidence: 86%
“…No significant changes in disability in Finland and declining disability prevalence have been reported in Spain (7). The CLESA collaborative study reports longer life expectancies and lower disability-free life expectancy in the older populations of Southern Europe than those in Northern Europe (8). To our knowledge, there is no report using longitudinal data on functional trends of the older population in Southern Europe.…”
Section: Introductionmentioning
confidence: 86%
“…However, disability rates are expected to increase in the future due to the aging of the population (Picavet and Hoeymans 2002). Southern Europeans are expected to spend a higher percentage of their lives with disability compared to the people from the north (Minicuci et al 2004). Nevertheless, Spain experienced a compression of disability and the postponement of severe disability onset to more advanced ages from the 1980s to the present (Zunzunegui et al 2006;Sagardui-Villamor et al 2005).…”
Section: Disability and Physical Functioning Trendsmentioning
confidence: 99%
“…Eikemo et al (2008) agreed with this conclusion. Minicuci et al (2004) argued in a somewhat similar manner, pointing to marked differences in educational status between northern and southern European countries, which translate into differences in occupational and economic status, which are themselves determinants for health outcomes, and which are also related to individual lifestyle, health care utilization, and risk behavior. Avendano et al (2009) emphasized that, for southern European countries, the association of socioeconomic status and education level with health status is especially strong, leading to less favorable results in the south.…”
Section: State Of Research: Health Inequalitiesmentioning
confidence: 90%
“…For instance, Ploubidis et al (2012) reported a north/south gradient for a measure of later life health in Europe modeled as a latent variable combining a total of nine self-rated and observer-measured health indicators, in which Scandinavian and western European countries (with considerable variation within this group) showed the best population health, while countries in the south exhibited the worst population health. Minicuci et al (2004) compared the prevalence of disability in daily living activities and found that its prevalence is lower among seniors in the Netherlands than in Spain and Italy. Other studies posited lesser amounts of inequality for some northern or western European countries (Chung and Muntaner 2007;Eikemo et al 2008) than elsewhere in Europe (Rostila 2007).…”
Section: State Of Research: Health Inequalitiesmentioning
confidence: 99%